O16 Access to gum clinics in the UK – a worsening picture?. (18th May 2015) - Prescott, Tim; Hayden, Vanessa; Foley, Elizabeth
Abstract : Background/introduction: In 2004 the Department of Health introduced a mandatory target for 100% of all patients in England to be offered 48-hour appointments by 2008. In 2010 these targets were removed and in April 2013 further changes to healthcare provision were introduced, with local authorities commissioning GUM (genitourinary medicine) services. Aim(s)/objectives: To assess the effect of recent commissioning changes to the accessibility to GUM clinics. Methods: During November 2014 male and female researchers telephoned all UK GUM clinics that were open for more than one day per week. Researchers contacted clinics twice: firstly presenting with symptoms consistent with an acute sexually transmitted infection and secondly requesting an appointment for an asymptomatic screen. Results: Of 236 clinics contacted, 89% could accommodate symptomatic 'patients' within 48 h with 53% of these on a walk-in basis only. Suggested waiting times ranged between 20 min and 3 h. 20% of asymptomatic 'patients' were unable to book an appointment and 58% of appointments were offered within 48 h. 86% of asymptomatic 'patients' were offered either a walk in service or appointment within 48 h. Discussion/conclusion: Overall 88% of 'patients' could be offered a time to be seen in a GUM clinic within 48 h, lower than last year's figure of 95% and the BASHH standard of 98%, suggesting service access has deteriorated. Further work will include a postal questionnaire to lead clinicians to evaluate their expectations on service access and visits to 33% of GUM clinics to explore the relationship between suggested waiting times and reality.